EFFECT OF SOME BOTANICAL PESTICIDES ON FEEDING ACTIVITY OF MICROTERMES NAJDENSIS (ISOPTERA: TERMITIDAE) - Alhemyari, A.A. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text